Quantitative real-time PCR and magnetic separation strategy for specific detection of group B streptococcus in perinatal Women's urine - Xu Tang; Lin-Ping Fan; Yang Liu (Practical Laboratory Medicine, 2024)
Introduction: Group B streptococcus(GBS)often causes adverse outcomes such as urinary system infection, intrauterine infection, premature birth, and stillbirth in perinatal women. Perinatal screening of GBS is conducive to guiding clinical scientific intervention and improving delivery outcomes.This study quantitative real-time PCR (RT-qPCR) combined with magnetic separation was used for GBS detection. Materials and methods: Sample pre-treatment in this study involved the utilization of magnetic separation (MS) technology, aiming to expedite the detection process and enhance detection sensitivity, and the cfb gene of group B streptococcus was used as the target gene to establish quantitative real-time PCR (RT-qPCR) to detect group B streptococcus. Results: It was found that penicillin-functionalized magnetic beads had a good ability to enrich and capture group B Streptococcus.The findings revealed an exceptional detection sensitivity, with the ability to detect B streptococcus in urine samples at levels as low as 102 CFU/mL. Conclusions: The utilization of MS technology in conjunction with the RT-qPCR (MS-RT-qPCR) assay, as demonstrated in this study, offers a viable approach for prenatal screening of group B streptococcus among perinatal women.